(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Karshya is a medical disorder where the body gradually becomes malnourished. An Apatarpanjanya Vyadhi, too. Karshya is considered to be one of the eight socially undesirable individuals named by Acharya Charka. The main causes of Karshya include Langhana, Rukshaannapana, vataprakopaka Ahara Vihar, among others. Each of them aggravates vata. Agni dushti, which results from vitiated vata, reduces the amount of Rasa dhatu and other dhatus that are produced, among other things. A person who is overly lean has thick nodes, dried-out buttocks, an empty stomach, and a neck with only traces of skin and bone. These are the primary clinical characteristics of Karshya that can be evaluated clinically using measures and linked to undernutrition to aid in correct therapy.